The Influence of Shopping Orientation, Online Trust, and Purchasing Experience on Purchasing Interests Back Through Consumer Satisfaction - Aris Ariyanto (Formosa Journal of Multidisciplinary Research, 2024)
The objective of this study was to investigate the potential impact of Shopping Orientation, Online Trust, and Purchase Experience on Repurchase Intention. This investigation aimed to identify whether these factors had an influence, either individually or collectively, either through the mediating variables of Consumer Satisfaction or directly. The research employed a descriptive quantitative methodology. The population for this study consisted of students enrolled in the Bachelor of Management programme at Pamulang University who made purchases at the TikTok Shop. A total of 250 respondents were selected as the sample. The data collection was conducted using a questionnaire, while the data analysis involved employing several techniques such as instrument testing, classic assumption testing, path testing, coefficient of determination, t-test, and arithmetic f-test. The findings of this study indicate that Shopping Orientation, Online Trust, and Purchase Experience have a positive and significant impact on TikTok Shop Consumer Satisfaction. Similarly, Shopping Orientation, Trust, Purchase Experience, and Consumer Satisfaction also have a positive and significant influence on Repurchase Intention on TikTok Shop.